Absorptive viscoelastic coatings for full field vibration coverage measurement in vibrothermography. (September 2016) - Vaddi, Jyani S.; Holland, Stephen D.; Kessler, Michael R.
Abstract: Vibrothermography is a rapidly emerging nondestructive evaluation technique for detecting fatigue cracks in aircraft components. Externally applied mechanical vibrations in a specimen generate crack heating between vibrating crack faces due to friction or other irreversible phenomena. Crack heating in vibrothermography depends on the vibrational stresses, and therefore the amount of vibration generated in the specimen. A method to measure the vibration distribution from the hysteretic heating of viscoelastic polymer adhesive applied to a specimen surface is described. The heat generated by the adhesive coating maps directly to the vibrational strain distribution in the substrate. This is a fast method of vibration coverage measurement for vibrothermographic testing. Abstract : Highlights: A novel method to measure vibration coverage in vibrothermography is proposed. Hysteretic heating in absorptive polymer coatings maps to dynamic strain in specimen. The coating heat can be calibrated to dynamic vibrational strain in the specimen. This method can also be used to identify the resonant mode the specimen is vibrated at.